SEED SIZE AND SEED QUALITY EFFECTS ON SEEDDLING GROWTH OF BARLEY VARIETIES GROWN IN Fe AND Zn DEFICIENT CALCAREOUS SOIL - Sadullah N. Al-NiemiSadullah N. Al-Niemi (Mesopotamia Journal of Agriculture)
Greenhouse experiment was carried out to study the effects of seed size and seed iron and zinc content on seedling growth of 15 promising and dominant varieties of barley plant in the North part of Iraq. Three groups of seed size with different seed quality (Fe and Zn content) of each variety were sown in Fe and Zn deficient alkaline calcareous soil. After six weeks root and shoot dry weights of barley plants grew from different seed size and seed quality were compared. Seedlings derived from larger seed size and with high Fe and Zn content had greater root and shoot dry weights. Barley varieties El-Kheir, 1/1105,Amal and local black performed better seedling growth.